ChemInform Abstract: Metal‐Catalyzed Amide Bond Forming Reactions in an Environmentally Friendly Aqueous Medium: Nitrile Hydrations and Beyond. Issue 16 (28th March 2013) - Garcia‐Alvarez, Rocio; Crochet, Pascale; Cadierno, Victorio
Abstract Review: 305 refs.